An efficient model for vehicle-slab track coupled dynamic analysis considering multiple slab cracks - Luo, Jun; Zhu, Shengyang; Zhai, Wanming (Construction & building materials, 2019)
•The vibration equation of multi-cracked track slab is deduced in time domain.•An efficient dynamic model for vehicle-slab track coupled system with multiple slab cracks is established.•Time-frequency analysis is conducted to evaluate the effect of the multiple slab cracks. This paper presents an efficient model for vehicle-slab track coupled dynamic analysis addressing the challenge problem of multiple slab cracks in high-speed railways. The multi-cracked track slabs are described as free Euler-Bernoulli beams supported on the cement asphalt (CA) mortar. The concentrated cracks are assumed to be in the through-transverse form, which are considered to locally affect the vertical bending stiffness of the beam and treated by applying the uniform flexural stiffness with Dirac’s delta singularities. The introduced damage parameters are expressed by incorporating the rotational springs using the linear elastic fracture mechanics. The vibration equations of slab track subsystem involving multiple slab cracks are finally set up by adopting the modal superposition approach, and are coupled with vehicle subsystem motions through nonlinear wheel-rail contact forces. An explicit integration method is applied to solve the whole coupled system excited by the random track irregularities. The developed model can also be expediently degenerated to the traditional model with intact slabs by setting the damage parameters to zero. Time-frequency analysis is conducted through fully investigating the effect of the crack depth, the crack numbers with different distribution properties and the CA mortar stiffness on the system dynamic responses. Some practical conclusions are drawn and may provide potent information for the maintenance in railway engineering and vibration based damage identification.